2020
DOI: 10.1111/coep.12504
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom and the Economic Consequences of the 1918 Pandemic

Abstract: The 1918 flu pandemic constituted an exogenous shock on economic activity. In this paper, we condition the economic importance of these shocks on the level of economic freedom measured by the Historical Index of Economic Liberty project to test whether freer economies fared better. Our argument is that higher levels of economic freedom meant a greater ability to adjust to shocks by reducing frictions in the reallocation of resources and the reorganization of economic activity. We find that higher levels of eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Specifications (1) and (2) are identical with the exception that the dependent variable is either the average change in GDP per capita during a pandemic or the average change in total GDP during a pandemic. Unsurprisingly and in conformity with findings of the economic effects of pandemics (Keogh‐Brown et al ., 2010; Barro et al ., 2020; Geloso and Bologna Pavlik, 2020), excess mortality slows down economic growth. The effect is only significant at the 10% level.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifications (1) and (2) are identical with the exception that the dependent variable is either the average change in GDP per capita during a pandemic or the average change in total GDP during a pandemic. Unsurprisingly and in conformity with findings of the economic effects of pandemics (Keogh‐Brown et al ., 2010; Barro et al ., 2020; Geloso and Bologna Pavlik, 2020), excess mortality slows down economic growth. The effect is only significant at the 10% level.…”
Section: Resultsmentioning
confidence: 99%
“…Using a differences‐in‐differences approach, they found that lives lost to natural causes (i.e., non‐COVID related such as septicemia, pneumonia, and diabetes) and to COVID‐19 fell by 15 per 100,000 residents on a weekly basis. Given that the cumulative number of deaths in pandemics is related to the extent of economic contractions (Barro et al ., 2020; Beach et al ., 2020; Geloso and Bologna Pavlik, 2020), their results suggest that CON laws might have seeped through to economic activity on a more macro‐level. Taking the sum of all similar interventions that limit the ability of businesses to adjust, and that is a large sum, suggests that governments can deepen economic shocks.…”
Section: Institutions Economic Freedom and Robustnessmentioning
confidence: 94%
See 3 more Smart Citations